Caracterización molecular de los integrones de clase1 en Protus mirabilis - Turina, Maria Adelaida (2015)
According to the data published by the CDC, there are 90.000 deaths per year in the US due to nosocomial infections. In recent years people talks about modern evolution, where not only come into play mutations as a major genetic mechanism to evolve and to make bacteria antimicrobial resistant, but also have revealed other mechanisms such as Lateral Genetic Transfer (LGT), which is a complex, multi-factorial and important mechanism in the evolution of various agents not only in bacteria. Antimicrobial resistance is the best example of the pressure-selection and genomic and phenotypic adaptation process based in LGT as approximately 80% of the resistances is due to LGT. By 1980, genetic elements associated to the acquisition and loss of genes were observed, which were identified as integrons. The current definition of integron defines it as an element that contains the genetic determinants to mediate site-specific recombination, being able to recognize and capture mobile genes cassettes, many of which encode determinants of antibiotic resistance.\nOur goal is to know the frequency of class 1 integrons and the gene cassette arrays in P. mirabilis as well as the evolution over 15 years into a collection of epidemiologically unrelated strains that are resistant to at least two antimicrobial families.\nThe study was conducted in 35 epidemiologically non related isolates of P. mirabilis from five hospitals of the Autonomous City of Buenos Aires and Buenos Aires province, isolated between 1993 and 2008. The selection criterion was that the isolates should be resistant to at least two antimicrobial families. It was determined the susceptibility of the studied isolates to eleven antimicrobials of clinical relevance by the agar disk diffusion method according to the guidelines of the National Committee for\nCaracterización Molecular del los Integrones de clase 1 en Proteus mirabilis\nBqca. M. A. TURINA|\nClinical Laboratory Standards (CLSI, 2013). To carry out the characterization of class 1 integrons, PCR mapping was performed by using different combinations of primers to characterize the structure and content of gene cassettes in the variable region.\nThe 91.43% of the isolates were resistant to ampicillin. Resistance to ceftazidime, cefotaxime and cefepime was evidenced in 48.57% of total isolates that had phenotype of CTX-M-2 extended spectrum ?-lactamase (ESBL). All the isolates were susceptibility to carbapenems. The 31.43% of the isolates were resistant to gentamicin, while 17.14% had intermediate susceptibility. Amikacin resistance was manifested in 91.43% of the isolates, 2.86% had intermediate susceptibility. Ciprofloxacin and nalidixic acid resistance in the studied isolates were 54.29% and 62.86% respectively. The percentage of resistance to trimethoprim / sulfamethoxazole was 91.43%.\nClass 1 integrons were found in 35/35 (100%) of the isolates, and ISCR1 was detected in 17/35 (48.57%) of them. 64 class 1 integrons were found in total in the 35 isolates, including 12 arrangements of different gene cassettes in their variable region, which include the combination of 9 genes cassettes, 8 of which correspond to antimicrobial resistant genes. The integrons found contain in their variable region an unfixed number of genes cassette. The arrangement of the most frequent genes cassette in the 35 isolates tested was aac (6 ') - Ib- blaOXA-2-orfD both in class 1complex and no complex integrons. Relating genes cassette arrangements of class 1 integrons with the results of antimicrobial susceptibility tested, it was observed that all isolates resistant to ceftazidime, cefotaxime and cefepime 17/35 (48.57%) have class 1 complex integrons that harbour ISCR1 with the blaCTX-M-2 gene in the VR-2.\nCaracterización Molecular del los Integrones de clase 1 en Proteus mirabilis\nBqca. M. A. TURINA|\nFrom a bioinformatic study, we observed that over a period of 20 years (1993-2013) 30 isolates of P. mirabilis with class 1 integrons were published in the Integrall database, in which 3 have class 1 complex integrons and that they are alone as such or as part of other structures such as genomic islands, plasmids and transposons. 34 class 1 integrons were found in them, with 27 arrangements of different genes cassette in their variable region, including the combination of 29 genes cassette, of which 25 correspond to antimicrobial resistant genes.\nIt was found in this collection of P. mirabilis from clinical isolates a high frequency of class 1 integrons 35/35 (100%) and ISCR1 was detected in 17/35 (48.57%) of them.\nWithin the complex class 1 integrons, In35::ISCR1::blaCTX-M-2 was the most frequent.\nIn the studied isolates for the period 1993-2008 although the amount of integrons by strain does not increase over the time with respect to the first isolates, it is observed a tendency to increase the number of families of antimicrobials that these isolates are resistant. Furthermore, the number of families of antimicrobial to which each strain is resistant depends on the gene cassette harbored in the integron structure more than the integrons number contained in the strain.\nOur results revealed once again that the LGT and with it the resistance to multiple antimicrobial families, is no longer exclusive patrimony of certain strains in particular.